HYDROLIC GROUNDWATER REGIMES ON RIVNE NPP IMPACT - Brovko, A.; Brovko, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of the research is to study and to analyze the groundwater regime in the aquifers of the Rivne NPP impacted area. The research is carried out on water intake data obtained from 21 monitored wells on the territory of Rivne NPP impact. There is studied groundwater regime in natural and man-made conditions. Fluctuations of groundwater level are determined mathematically using correlation and regression analysis. There is given environmental assessment of the research area and the area of Rivne NPP. The paper analyzes annual groundwater cycle in different aquifers. The findings reveal: (1) aquifer regime in the Quaternary deposits to have a seasonal type of recharge; (2) aquifer regime in the Upper Cretaceous deposits to have a seasonal type of recharge and be invariant of water intakes in the area of Rivne NPP impact; (3) aquifer regime in the Upper Proterozoic deposits to have a seasonal type of recharge and be variant of water intakes in this area.